Aplicación del modelo de psicoterapia breve intensiva de Leopold Bellak con mujeres en situación de violencia intrafamiliar que acuden al Centro de Equidad y Justicia de Calderón entre mayo y agosto de 2015 - Fuertes Lagos, Alexandra Elizabeth (2016)
Women in situations of domestic violence are the segment of the population widely demanding psychological care at the Centro de Equidad y Justicia de Calderón. To respond to this requirement, the application of the Intensive Brief Psychotherapy by Leopold Bellak is proposed. This model consists of 5 therapeutic sessions, plus a follow-up appointment, in which an entire understanding of the person is sought; main symptoms are identified and progressively treated in a positive therapeutic relationship. This project includes specific sessions and tools for assessment and data collection. To validate the use of the Intensive Brief Psychotherapy, and deducing care guidelines for abused women in similar contexts, a sequence of sessions, used instruments, main symptoms, areas and methods of intervention and psychological results in each process are presented. It is ascertained that focusing and planning the intervention, as well as establishing a therapeutic alliance, propitiate positive results, including: adherence of the beneficiaries to the intervention, positive changes in their mood and family ties, formation of social support networks and deeper awareness of violent situations. The model shows up particularly efficacy to attend depressive states and to increase ego functioning, however not to produce profound personality changes.